The effect of personality characteristics on the facial esthetic satisfaction of edentulous patients - TANG Jinxin, TANG Chunbo, LANG Yiyuan, RUI Na, WANG Chen (Editorial Office of Stomatology, 2024)
Objective To explore the effect of personality characteristics on the facial esthetic satisfaction of edentulous patients, in order to provide reference for improving esthetic satisfaction after complete denture restoration. Methods Twenty-two edentulous subjects were randomly selected. Before complete denture treatment, the emotional stability of patients was assessed by Eysenck personality questionnaire N scale score(EPQ-N). Before and three months after treatment, patients completed the orofacial esthetic questionnaire, and 3D stereophotogrammetry was performed to evaluate the changes in facial appearance. In addition, multiple linear regression model was established by using N scale score, changes in facial appearance and facial esthetic satisfaction score. Results After complete denture treatment, the difference in the ratio of the middle and lower parts of the face between patients and the normal group was reduced by (3.85±2.63)%, and the difference of the nasolabial angle between patients and the normal group was reduced by (6.66°±5.39°). The multiple linear regression model showed that N scale score and changes of the differencein the facial proportion between edentulous subjects and normal population were influencing factors of patients' esthetic satisfaction on the facial appearance, and the N scale score and changes of the difference inthe nasolabial anglebetween patients and normal population were influencing factors of the patients' aesthetic satisfaction on the facial profile. Moreover, the effect of two independent variables(N scale score and facial soft tissue change)on the aesthetic satisfaction of facial appearance and facial profile was statistically significant(P<0.001). Furthermore, when the N score increased, the patients' aesthetic satisfaction on the facial appearance and facial profile decreased(B<0). Conclusion Personality can affect the aesthetic satisfaction of edentulous patients. Consequently, we should take reasonable measures for patients with different personality in the process of complete denture restoration, so as to achieve the goal of improving patients' aesthetic satisfaction.